Influence of Cementation Level on the Mechanical Behavior of Bio-cemented Slope Soil Treated by Surface Injection - Gowthaman, S.; Chen, M.; Nakashima, K.; Kawasaki, S. (3rd International Conference in Geotechnical Engineering (ICGE), Sri Lankan Geotechnical Society, 2021)
Bio-cementation has recently emerged as a novel soil stabilization technique that can improve mechanical behaviors of soil in a sustainable way. The contact cementation is induced by ureolytic soil bacteria through a set of bio-geochemical processes, leading to the formation of a stiff soil skeleton. The objective of this paper is to study the mechanical behavior of slope soil treated to varying cementation levels ranging from uncemented soil to heavily cemented sandstone like conditions. The unconfined compression test results suggest that the strength and stiffness of the soil increase with the increase in cementation level. As the cementation increased, the peak state was reached at lower axial strains, suggesting the increase in brittleness. Permeability results shows a linear decrease with the increase in cementation level. The bio-clogging mechanism also has been well demonstrated by SEM (Scanning Electron Microscopy). The outcomes of this study have deepened the understanding in specifying the desired treatment level for slope soil stabilization purpose.